2009
DOI: 10.1002/jmri.21884
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted imaging of breast cancer: Correlation of the apparent diffusion coefficient value with prognostic factors

Abstract: Purpose:To evaluate the role of diffusion-weighted imaging (DWI) in the detection of breast cancers, and to correlate the apparent diffusion coefficient (ADC) value with prognostic factors. Materials and Methods:Sixty-seven women with invasive cancer underwent breast MRI. Histological specimens were analyzed for tumor size and grade, and expression of estrogen receptors (ER), progesterone receptors, c-erbB-2, p53, Ki-67, and epidermal growth factor receptors. The computed mean ADC values of breast cancer and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
159
7
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(188 citation statements)
references
References 19 publications
13
159
7
7
Order By: Relevance
“…Breast MRI is an established supplemental technique to mammography and ultrasonography for evaluation of suspicious breast lesions. Diffusion-weighted MRI (DWI) has recently been integrated into the standard breast MRI for discrimination of benign and malignant breast lesions obtained with dynamic contrast-enhanced MRI [1][2][3][4][5][6][7][8][9][10][11][12][13]. DWI is a non-invasive technique that represents the biological character of the mainly Brownian movement of protons in bulk water molecules in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Breast MRI is an established supplemental technique to mammography and ultrasonography for evaluation of suspicious breast lesions. Diffusion-weighted MRI (DWI) has recently been integrated into the standard breast MRI for discrimination of benign and malignant breast lesions obtained with dynamic contrast-enhanced MRI [1][2][3][4][5][6][7][8][9][10][11][12][13]. DWI is a non-invasive technique that represents the biological character of the mainly Brownian movement of protons in bulk water molecules in vivo.…”
mentioning
confidence: 99%
“…Classic prognostic markers, including tumour size and grade, and lymph node status in patients with breast cancer, and molecular markers, including oestrogen receptor (ER), progesterone receptor (PR), index, human growth factor receptor 2 (HER2) protein and angiogenic molecular markers, have been reported [1,15,16]. Few studies have examined the correlation between ADC values and prognostic factors [1,8]. The purpose of this study is to compare ADC values of DWI of breast cancer with prognostic factors.…”
mentioning
confidence: 99%
“…This finding is not consistent with that of a previous study by Tozaki et al (36) who found that segmental distribution, heterogeneous internal enhancement, and clustered ring enhancement were the most frequent findings in malignant NME. Some specific tumor subtypes, such as papillary carcinoma, are associated with the lowest ADC values among malignant breast tumors (37). On the other hand, their ADC values are very similar to those observed for benign papillomas (38), indicating the histologic similarity between benign and malignant papillary lesions.…”
Section: Discussionmentioning
confidence: 79%
“…Under the pathological conditions, the alterations of tissue microenvironment, such as loss of membrane integrity and distribution changes of macromolecule, may change the rates of water molecules diffusion, and finally it may present in the image of DWI (Woodhams et al, 2011). Moreover, ADC value was considered as one of the most important quantitative parameters of DWI to reflect the mobility of water molecules in biological tissues, which has shown to be decreased in various malignancies of different organs (Kim et al, 2009;Padhani et al, 2009). Consequently, DWI with ADC values can be regarded as a useful method in the diagnosis and quantitative measurement of neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…DWI, as a modality utilized to assess the microstructural characteristics of water diffusion in biological tissues, has been increasingly applied to evaluation the development of tumors in the body (Koh et al, 2007;Kim et al, 2009). The application of DWI is based on the principle that water molecules could explore tissue structures at a microscopic scale which is surpass the ordinary image resolution in the process of their random diffusion-driven displacements (Le Bihan et al, 2001;Cosottini et al, 2005).…”
Section: Introductionmentioning
confidence: 99%